Tinjauan Atas Prosedur Flagging Peserta Taspen Dalam Rangka Pengajuan Kredit: Studi Kasus Pada PT. Bank BJB KCP Cicurug - Arif, Bahtiar; Agustin, Indri Yani; Munawar, R. Aang (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Flagging is the giving of a sign or binding to a customer so that the customer is not easily moved or taken over by a bank or other financial institution as long as the customer still has loans at the related bank. The process of marking or binding is carried out on the related bank database system for verification by the first party.The purpose of this research is to find out the Flagging Procedures for Taspen Participants in the Context of Applying for Credit at PT. West Java and Banten Regional Development Bank, Tbk. KCP Cicurug. In order to achieve clear and directed research objectives, the authors formulate the problems that will be discussed regarding the flagging procedure for Taspen participants in the context of applying for credit, the flagging procedure for Taspen participants in the context of applying for credit is in accordance with the SOP of Bank BJB KCP Cicurug.Based on the results of the research and discussion, the flagging procedure for Taspen participants in the context of applying for credit at Bank BJB KCP Cicurug is carried out simultaneously with the credit agreement. Debtors who are participants in this taspen only need to fill out an approval form or a flagging form when the debtor enters into a credit agreement. Flagging carried out by Bank BJB KCP Cicurug is carried out for Civil Servant debtors who have a fixed salary and as taspen participants who will later be bound by Bank BJB KCP Cicurug so that these debtors cannot move to other banks or institutions as long as they still have loans at Bank BJB KCP Cicurug. Flagging is carried out by Bank BJB KCP Cicurug officers through the flagging.taspen.co.id website. Then when Bank BJB KCP Cicurug officers flagged a debtor, the data filled in must be in accordance with the form filled out by the previous debtor so that the flagging carried out for the debtor is approved by the first party.